If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(3-4x)-28x-1)=12x
We move all terms to the left:
-4(3-4x)-28x-1)-(12x)=0
We add all the numbers together, and all the variables
-4(-4x+3)-28x-1)-12x=0
We add all the numbers together, and all the variables
-28x-4(-4x+3)-1)-12x=0
We multiply parentheses
-28x+16x-1)-12x-12=0
We add all the numbers together, and all the variables
-12x-1)-12x-12=0
| X/4=11+(4x2) | | x2−12x=28 | | 2x(10-x)=4 | | 1/30=x/1 | | 24x+28=2 | | 10+19=x2 | | 3-4*7+4=x | | 6x+28=15 | | M=m4-2m+1 | | 6=w-2/5+9w-6/2= | | 45x+74=325 | | 3-4*2+3=x | | -24=16+x | | 16x-320=920 | | 2x-9-7=30 | | 2x-9-7=90 | | 5x+7=8x-2,x= | | r/3+5=8 | | 7c-1=5c+13 | | -x+10x^2=x^2+16x | | x+1/x+3=15/21 | | x-1/5=8x/35 | | 10a+17=9 | | 3-2n=17+5= | | (x-1)/5=8x/35 | | -1/2=-2/5y-5/7 | | 13=(4u-5/6)+(9u+7/2) | | 0=2(x+3)(x+3)-6 | | x/3−1/2=5/6 | | x/4+1/3=7/12 | | 0=-(x-3)(x-3)+9 | | (2x-12)+(x-12)=42 |